Cardiovascular, cerebrovascular, and respiratory changes induced by different types of music in musicians and non-musicians: the importance of silence. Issue 4 (30th September 2005) - Bernardi, L; Porta, C; Sleight, P
Abstract : Objective: To assess the potential clinical use, particularly in modulating stress, of changes in the cardiovascular and respiratory systems induced by music, specifically tempo, rhythm, melodic structure, pause, individual preference, habituation, order effect of presentation, and previous musical training. Design: Measurement of cardiovascular and respiratory variables while patients listened to music. Setting: University research laboratory for the study of cardiorespiratory autonomic function. Patients: 12 practising musicians and 12 age matched controls. Interventions: After a five minute baseline, presentation in random order of six different music styles (first for a two minute, then for a four minute track), with a randomly inserted two minute pause, in either sequence. Main outcome measures: Breathing rate, ventilation, carbon dioxide, RR interval, blood pressure, mid-cerebral artery flow velocity, and baroreflex. Results: Ventilation, blood pressure, and heart rate increased and mid-cerebral artery flow velocity and baroreflex decreased with faster tempi and simpler rhythmic structures compared with baseline. No habituation effect was seen. The pause reduced heart rate, blood pressure, and minute ventilation, even below baseline. An order effect independent of style was evident for mid-cerebral artery flow velocity, indicating a progressive reduction with exposure to music, independent of style. Musicians had greater respiratory sensitivity to the music tempo than did non-musicians. Conclusions: Music induces an arousal effect, predominantly related to the tempo. Slow or meditative music can induce a relaxing effect; relaxation is particularly evident during a pause. Music, especially in trained subjects, may first concentrate attention during faster rhythms, then induce relaxation during pauses or slower rhythms.